Borderscape: (re)defining the customs - Sotiriou, Steven (My University, 2011)
Within the present South African context, we continue to be defined, threatened, controlled, sheltered and challenged by the factor of borders. While the border may be the separation of one nation from another, its is also a joint where people interact, trade and communicate. This forum emerges as a new hybrid landscape - a third space, where state and people meet beyond the separation of border. This project addresses the collective ambit of borderscape as a third space. It aims to develop a transnational space with appropriate permeability and synergy, integrating landscape, infrastructure and programme, while simultaneously capturing the efficiency and poetry of crossing the border, within the everyday. While prevailing trends continue to point towards heightened levels of border security, the accommodation of the everyday within the border experience, is a congruent priority. Questions of emphasis arise - challenging the direction and basis of borders